Alistipes and Eggerthella shape the response to oncolytic adenovirus therapy in mice and humans through short-chain fatty acid metabolism - van der Heijden; Mirte; Armstrong Clubb; James Hugo; Erawijantari, Pande Putu; Ronkainen, Aki; Arias, Victor; Jirovec, Elise; Kudling, Tatiana; Pakola, Santeri Artturi; Ojala, Nea; Haybout, Lyna; et al. (Taylor & Francis, 2026)
Accumulating evidence implicates the microbiome as an important determinant of clinical outcomes in cancer therapies; however, the role of the microbiome in oncolytic virus therapy remains largely unexplored. We investigated the gut microbiome of cancer patients following treatment with the oncolytic adenovirus igrelimogene litadenorepvec (Ad5/3-E2F-d24-hTNF-IRES-hIL2; TILT-123). Baseline fecal samples from phase I clinical trials (NCT04695327 and NCT05271318) were analyzed using shotgun metagenomic sequencing and compared to treatment outcomes. A higher relative abundance of Alistipes was observed in patients with treatment benefit, while elevated Eggerthella was observed with reduced benefit. These associations were validated in a preclinical mouse model where administration of Alistipes shahii improved the efficacy of adenovirus therapy. In addition, enrichment analysis in patient samples showed a positive correlation between higher relative abundance of Alistipes and elevated short-chain fatty acids in both feces and serum, which in turn revealed higher circulating neutrophil counts. Finally, in a case study, we observed that adenovirus treatment resulted in increased Alistipes relative abundance and reduced Eggerthella relative abundance, indicating that adenovirus therapy may beneficially modulate the microbiome. Overall, our findings reveal a novel association between Alistipes, Eggerthella, and the therapeutic response to oncolytic adenovirus therapy, highlighting their potential as biomarkers or targets for microbiome-based interventions such as pre-, pro-, or postbiotics.